Risk factors of the thyroid cancer - Joanna Miśkiewicz; Aleksandra Ciuła; Anna Jakubiak; grzegorz Karaban; Monika Paszkowska; Michał Borawski; Klaudia Mularczyk; Patrycja Znamirowska; Tadeusz Kuźnieców; Magdalena Kupis (Quality in Sport)
Introduction and purpose: These days, thyroid cancer (TC) is the most common endocrine cancer. According to ,,Cancer in Poland in 2022” thyroid cancer affected 47800 women in 2022. A better understanding of the illness will help develop more potent treatment and prevention strategies. The goal of our work is to classify and describe risk factors [RF] for TC.